DAKWAH MULTIKULTURAL KIAI PEDESAAN DI ERA MODERN - Hindy Rahma Mufida; Ahmad Nurcholis (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
Abstract: Seeing increasingly rapid development of Islam certainly does not escape the existence of various conflicts that become obstacles. Focused Islamic da’wah spreading about messages that refer to rast’s religious values will directly intersect with existing social conditions. Especially within the scope. In rural areas with a large number of residents, of course there is diversity wich can create new problems. Difference in art. Religion and ethnicity can lead to confusion caused by differences in understanding. In addition, the rapid development of technology has become a very influential thing in the process of Islamic development. So it is necessary to have the right follow up in preaching to realize a peaceful Islam an rahmatan lil alamin. In order for Islamic da’wah to develop, it is necessary to maintain and mobilize it in line with the times. So a preacher must be able to balance between culture and media. Because the increasingly sophisticated technological media in this modern era will be of great help in preaching. Melihat perkembangan Islam yang semakin pesat tentu tidak luput dari adanya berbagai konflik yang menjadi penghambat. Dakwah Islam yang fokus menyebarkan tentang pesan yang mengacu pada nilai-nilai agama pasti akan bersinggungan langsung dengan kondisi sosial yang ada. Terutama dalam lingkup lokal pedesaan dengan banyak penduduk tentu ada keberagaman yang dapat memunculkan masalah baru. Perbedaan seni, budaya, agama dan etnis dapat mengakibatkan kekacauan yang disebabkan oleh perbedaan dalam pemahaman. Selain itu, pesatnya perkembangan teknologi menjadi suatu hal yang sangat berpengaruh dalam proses perkembangan Islam. Sehingga perlu adanya tindak lanjut yang tepat dalam dakwah untuk mewujudkan Islam yang damai dan rahmatan lil alamin. Agar dakwah Islam dapat berkembang, maka perlu untuk memelihara dan menggerakannya seiring dengan perkembangan zaman. Maka seorang pendakwah harus bisa menyeimbangkan antara budaya dan media. Karena semakin canggihnya media teknologi di era modern ini akan sangat membantu dalam dakwah].